1950
DOI: 10.1161/01.cir.2.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Tests in Chronic Congestive Heart Failure

Abstract: It has been difficult for the clinician to evaluate quantitatively and qualitatively the degree of damage to the liver in the presence of congestive heart failure. This paper gives a statistical analysis of the results of various liver function tests on a group of patients with congestive heart failure. The analysis includes comparisons based on etiology, type of rhythm, duration of heart failure, and nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1955
1955
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…The occurrence of jaundice in patients with both acute and chronic heart failure has been noted for many years (Jolliffe, 1930;Kugel and Lichtman, 1933;Felder, Mund, and Parker, 1950;Sherlock, 1951;Evans, Zimmerman, Wilmer, Thomas, and Ethridge, 1952;White, Leevy, Brusca, and Gnassi, 1955;Richman, Delman, and Grob, 1961). Jaundice following non-cardiac surgery and injury has also been reported (Geller and Tagnon, 1950;Sevitt, 1958;Pichlmayr and Stich, 1962;Schmid, Hefti, Gattiker, Kistler, and Senning, 1965).…”
mentioning
confidence: 99%
“…The occurrence of jaundice in patients with both acute and chronic heart failure has been noted for many years (Jolliffe, 1930;Kugel and Lichtman, 1933;Felder, Mund, and Parker, 1950;Sherlock, 1951;Evans, Zimmerman, Wilmer, Thomas, and Ethridge, 1952;White, Leevy, Brusca, and Gnassi, 1955;Richman, Delman, and Grob, 1961). Jaundice following non-cardiac surgery and injury has also been reported (Geller and Tagnon, 1950;Sevitt, 1958;Pichlmayr and Stich, 1962;Schmid, Hefti, Gattiker, Kistler, and Senning, 1965).…”
mentioning
confidence: 99%
“…Fredericks & Hoffbauer (1945) found that in eleven subjects receiving malarial therapy, BSP retention occurred in eight ;Felder, Mund & Parker (1950) observed that in 135 cases of 'chronic protracted congestive heart failure' BSP clearance was 'normal in 85 % of the determinations', and Jolliffe (1930) found no constant relation between the clinical state of patients in heart failure and the BSP clearance.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] ). Concerning T-BIL, according Shinigava et al the prevalence of abnormal serum levels was much higher (64%) compared to work of Lau et al (19%) and this study (34%).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, there are only few works investigating the liver involvement in AHF (Table 1) (ref. [6][7][8][9][10][11][12][13][14]. The aim of this study was to evaluate the prevalence of LFTs abnormalities and to identify associated cardiac and noncardiac factors mediating hepatic impairment in AHF -new onset (de novo) heart failure as well as acute exacerbation of chronic.…”
Section: Introductionmentioning
confidence: 99%